2015
DOI: 10.1111/1365-2664.12386
|View full text |Cite
|
Sign up to set email alerts
|

EDITOR'S CHOICE: Competition on the range: science vs. perception in a bison–cattle conflict in the western USA

Abstract: 1. Competition between livestock and wild ungulates is commonly perceived to occur on shared rangelands. In the Henry Mountains (HM) of Utah, a free-ranging population of bison Bison bison has raised concerns among ranchers holding grazing permits on these public lands. Bison are the most conspicuous potential competitors with cattle, but lagomorphs (mainly jackrabbits Lepus californicus) are also abundant in this area. The local ranching community is applying political pressure on state and federal agencies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
(35 reference statements)
0
35
0
1
Order By: Relevance
“…In some cases this is beginning to happen where agencies are realizing that building local support is the key to cooperative efforts that minimize the potential for legal challenges. Competition between wildlife and livestock can be both actual and perceived, with perceived competition prevailing especially where livestock owners-and sometimes land owners-derive no tangible benefits from wildlife (Ranglack et al 2015). The absence of benefits is likely because they are not allowed by commandand-control laws administered by government agencies.…”
Section: Societal Implications Of Integrating the Management Of Wildlmentioning
confidence: 99%
“…In some cases this is beginning to happen where agencies are realizing that building local support is the key to cooperative efforts that minimize the potential for legal challenges. Competition between wildlife and livestock can be both actual and perceived, with perceived competition prevailing especially where livestock owners-and sometimes land owners-derive no tangible benefits from wildlife (Ranglack et al 2015). The absence of benefits is likely because they are not allowed by commandand-control laws administered by government agencies.…”
Section: Societal Implications Of Integrating the Management Of Wildlmentioning
confidence: 99%
“…Black‐tailed jackrabbits can consume large amounts of grass seedlings in semiarid shrublands, as shown by McAdoo, Longland, Cluff, and Klebenow () at a study site in the Great Basin in Nevada. Even in comparison with much larger herbivores (bison), Ranglack et al () demonstrated that grass consumption by black‐tailed jackrabbits in Utah can be considerable, accounting for 34.1% of grass consumption compared to 13.7% from bison. However, Daniel et al () showed that black‐tailed jackrabbits in the Chihuahuan Desert primarily consume shrubs, which constituted 47% of their diet.…”
Section: Discussionmentioning
confidence: 99%
“…One source of biotic feedbacks may be herbivory from small mammals, especially rodents and lagomorphs, which suppresses grass reestablishment in shrub‐invaded grasslands and influences vegetation structure and plant assemblages (Heske, Brown, & Guo, ; Roth, Whitford, & Steinberger, ). In addition to suppressing grass establishment, lagomorphs can consume substantive amounts of grass biomass and otherwise change spatial patterns of herbaceous growth (Marko, Onodi, Kertesz, & Altbacker, ; Ranglack, Durham, & Toit, ). As the herbaceous plant cover between shrubs decreases and shrub densities increase, the forage conditions can become more favorable for small mammals due to reduced predation risk (Thompson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ranchers and cattle have shared the HM with bison since their introduction, and given their high dietary overlap and ecological similarity (van Vuren and Bray 1983, Allred et al 2011, Kohl et al 2013, there is strong potential for cattle to compete with bison for forage and impact their population dynamics on shared rangelands, but we could not account for such effects given the lack of data on the number of cattle that have actually used the HM each year. Using a unique combination of experimental exclosure and space-use studies, however, our colleagues are finding that competition between bison and cattle for forage on the HM is minimal under recent environmental conditions (Ranglack et al 2015; H. Ranglack and J. T. du Toit, unpublished manuscript); perhaps because cattle must remain near limited sources of water, while bison can range more freely (van Vuren 2001). Complex interactions between climate, phenology, and primary productivity, as well as transient fluctuations in age and sex structure induced by extractions (Buhnerkempe et al 2011) might help explain greater amounts of variability in bison population dynamics in the HM.…”
Section: Discussionmentioning
confidence: 99%